New graduate medication safety preparedness: an Australian cross-sectional and longitudinal qualitative research study - Ottrey, Ella; Rees, Charlotte E.; Lyons, Kayley M.; Brock, Tina P.; Monrouxe, Lynn V.; Harrison, Claire; Morphet, Julia (Frontiers in Medicine, 2026)
IntroductionPatient safety is paramount, yet medication management errors are common, including amongst new graduates. Ongoing need exists to examine new graduates’ medication safety preparedness, to better improve preparedness and help them manage medication errors. This cross-sectional and longitudinal qualitative research (LQR) explores new graduates’ medication safety preparedness in nursing, pharmacy and medicine.MethodsUnderpinned by social constructionism, 26 final-year healthcare students at an Australian university participated in three study phases between July 2019 and April 2020: entrance interviews (around degree completion), longitudinal audio-diaries (through approximately the first 12 weeks of work), and exit interviews (after approximately 12 weeks of work). We analyzed interview and audio-diary transcripts, and audio-diary email correspondence using team-based framework analysis, cross-sectionally and longitudinally.ResultsParticipants’ medication safety stories demonstrated mostly unpreparedness, often about developing and implementing medication therapy plans. Medication error narratives revealed errors (of commission or omission) made by new graduates or others. They were rich in emotional talk (mostly negative such as anxiety, anger and sadness talk), illustrating psychosocial impacts on new graduates. However, positive emotional talk was also present in preparedness stories. While the proportion of preparedness stories increased across time at the cohort level, we found more nuanced/complex patterning in participants’ narratives at the individual level including evidence of stability, and positive or negative changes in medication safety preparedness.DiscussionWe offer evidence-based recommendations for student/new graduate learning to help educators better prepare them for medication safety and enable them to cope with the emotional work of safe medication management. Further LQR with longer study durations is now needed on medication safety preparedness.